An empirical study of the use of cost accounting systems in the Libyan agricultural firms - Fatah, Abobaker M Abdurahman (2013)
The agricultural sector is one of the important contributors to Libyan economy. Most of the agricultural firms in Libya are government-owned and recently compelled to compete with foreign companies. Available literature shows that one of the challenges faced by the government-owned agricultural firms in Libya is the ever-increasing production costs. This results in the reduction of the country’s wheat production as the market price decreases. The importance of understanding the impact of the increasing costs motivates the thesis to investigate the nature of cost accounting systems in the agricultural firms which receives less attention than the manufacturing sector. The main objective of the thesis is to examine and understand the current practice of cost accounting systems in Libyan agricultural firms. Using a mixed-method explanatory design, three instruments were used to collect the data, namely a questionnaire-based survey, interviews and documentation analysis. A total of 57 questionnaires were distributed to government-owned agricultural firms in Libya. In addition, interviews with management accountants and documentation analysis were conducted to support the findings. A framework was developed based on the survey findings, which includes the influence of six contingent factors on the use of cost accounting systems. This study found that the firm size, cost structure, importance of cost information and legal obligation positively and significantly influence Libyan agricultural firms to use cost accounting systems. The influence of both competition and product diversity, on the other hand are not significant. The results of the study are expected to have implications for Libyan agricultural firms regarding the importance of using cost accounting systems in managing their production costs